O som do teu olhar: fragmentos sobre a construção de uma novela - Kanesiro, Harini Abja (2020)
This master’s thesis is composed of two parts: a novella and a theoretical essay, written in fragments, on the process of creating the fictional text. The essay seeks, first of all, to offer a glimpse on the writing of the novella “O som do teu olhar”, reflecting on the creative gesture and explaining in what ways theory can contribute to fiction, establishing dialogues with Walter Benjamin, Luiz Antonio de Assis Brasil, Ernst Hemingway, and others. The novel tells Greta Batalha’s story, a young woman from São Paulo and a master’s student in Anthropology, who suffers through a very intense love breakup, without much explanation, from Miguel. Raised by her grandparents and accompanied by Laura, a friend with a difficult temper, Greta returns to the past in her reminiscences, seeking answers about the separations and abandonments that rule her life. While it is true that she finds sadness in her story and more questions than answers, she is also surprised by important details that feed her hope that the future can be better. Throughout the narrative, Greta meets a lady named Anke, with whom she shares impressions about life, and with whom she tries to learn the affection and tenderness she seeks so much in others.